Apical Leakage of Different Gutta-Percha Techniques: Thermafil, Js Quick-Fill, Soft Core, Microseal, System B and Lateral Condensation with a Computerized Fluid Filtration Meter - Gençoğlu, Nimet; Oruçoğlu, Hasan; Helvacıoğlu, Dilek (European Journal of Dentistry, 2007)
Objectives: To investigate apical leakage of roots filled with 6 different gutta-percha techniques; Thermafil, JS Quick-Fill, Soft Core, Microseal, System B and lateral condensation using a new computerized filtration meter.Methods: Materials and Methods: 60 extracted single rooted teeth were used. Coronal part of each tooth was removed and the root canals were prepared with step-back technique. The roots were randomly divided into six groups of 10 teeth, filled by one of the obturation technique and Kerr sealer. The teeth were kept in 100% humidity for 2 years. After this period, apical parts of roots (10±0.05 mm) were attached to computerized fluid filtration meter. Apical leakage quantity was determined as μl.cmH2O-1.min-1.Results: Statistical analysis indicated that Thermafil, Soft Core, Quick-Fill and System B techniques showed lower leakage than Microseal and lateral condensation (P>.05). However, statistically no difference was found among the core techniques and no difference was found between microseal and lateral condensation techniques (P>.05).Conclusions: Thermafil, Soft Core,Quick-Fill and System B techniques showed lower leakage than Microseal and lateral condensation. In addition, this new computerized fluid filtration meter allowed quantitative measurement of leakage easily. (Eur J Dent 2007;2:97-103)
Keywords: Fluid filtration; JS Quick-Fill; Microseal; System B; Thermafil; Lateral condensation